Peran konstitusi dalam mewujudkan kontitusionalisme: di indonesia - IDRIS, MOH (Maliki Interdisciplinary Journal, 2025)
This study examines the role of the constitution and the Constitutional Court (MK) in upholding the principles of constitutionalism in the Indonesian state system. The Constitution serves as the supreme law that regulates the power structure, guarantees human rights, and limits the authority of state institutions through a mechanism of checks and balances. The Constitutional Court, as the guardian of the constitution, has the primary authority to review laws, resolve disputes over authority between state institutions, decide on election disputes, and decide on the dissolution of political parties. Through these authorities, the Constitutional Court acts as a bulwark in maintaining the supremacy of the constitution and protecting the constitutional rights of citizens. However, the implementation of constitutionalism still faces several challenges, such as political pressure, low public understanding of the Constitutional Court’s function, and issues of integrity among law enforcement officials. This study emphasizes that the effectiveness of constitutionalism requires fairly enforced laws, an independent judiciary, and active public participation to strengthen a democratic legal culture.